Plateau is a prognostic factor of lenalidomide therapy for previously treated multiple myeloma. Issue 3 (28th March 2021) - Takakuwa, Teruhito; Ohta, Kensuke; Nakatani, Eiji; Ito, Tomoki; Kaneko, Hitomi; Fuchida, Shin‐Ichi; Shimura, Yuji; Yagi, Hideo; Shibayama, Hirohiko; Kanda, Junya; Uchiyama, Hitoji; Kosugi, Satoru; et al.
Abstract: The plateau phase emerging during the treatment of multiple myeloma (MM) is known to last steadily for a certain period, even without treatment. Therefore, the treatment started at plateau phase is expected to be associated with a better outcome. In this study, this hypothesis was evaluated retrospectively for previously treated MM patients in Kansai Myeloma Forum database who received lenalidomide (LEN) with or without dexamethasone for the first time. Disease stability index (DSI) was defined as (maximum – minimum values of M protein during the 90 days before the start of LEN) divided by M‐protein values at the start of LEN. The patients were classified into three groups: stable (S), DSI ≤ 0.25; increasing (I), DSI > 0.25 with increasing M protein; decreasing (D), DSI > 0.25 with decreasing M protein. In univariate analysis of 352 patients, DSI group "I", non‐IgG type, serum albumin<3.5 g/dL, and age≥70 were statistically significant prognostic factors for both progression‐free survival and overall survival. In multivariate analysis, the former 3 risk factors were statistically significant for poor overall survival. Thus, DSI is an independent prognostic factor for the treatment with LEN for previously treated MM.